Penggunaan Electronic Word of Mouth (eWOM) untuk Berbagi Pengalaman Kuliner oleh Wisatawan - Agusta Ika Prihanti Nugraheni; Lana Prihanti Putri; Neni Pancawati (Tourism Scientific Journal, 2021)
Tourist behavior has developed not only in the planning, decision-making and purchasing phases, but also in sharing their experiences after the trip. Social media platforms allow tourists to digitize and share knowledge, experiences, emotions and precious moments and suggestions, even criticism. The impact of eWOM on the hospitality industry is very strong. The culinary industry, such as restaurant services, cannot be evaluated before the experience is consumed, so intangible purchases of products and services carry a higher risk, consequently customers are more dependent on the interpersonal influence of eWOM in making decisions. This study aims to identify the characteristics of tourists who often do posttrip sharing experiences and the types of messages used with culinary tourism purposes and their role in eWOM by using explorative descriptive quantitative research. The data gathered using questionnaire which is given to 100 respondents, but only 93 survey results were considered valid. The results showed that the millennial generation and generation Z, and those originally from big cities posted their experiences most after the trip and 80% of respondents used both visual and narrative content in sharing their experiences. There is a considerable increase in the use of the tiktok social media platform for sharing tourist experiences, particularly among generation Z and there has been no significant change in the sharing of culinary experiences on social media as a result of the covid 19 pandemic. It is even possible to see an increase in online sharing as a result of the increased use of technology.